2014
DOI: 10.1007/s12325-014-0159-z
|View full text |Cite
|
Sign up to set email alerts
|

Improved Response Rates with Bortezomib in Relapsed or Refractory Multiple Myeloma: An Observational Study in Chinese Patients

Abstract: IntroductionBortezomib, a novel proteasome inhibitor, is approved for the treatment of relapsed multiple myeloma (MM). Efficacy and safety of bortezomib is well known; however, it was necessary to validate the data in patients with different ethnic backgrounds. The efficacy and safety of bortezomib was assessed in patients from China with relapsed/refractory MM in a real-world scenario.MethodsThis prospective, non-interventional, observational study enrolled both male and female Chinese patients, aged ≥18 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Of the evaluable Taiwanese patients with MM, the majority demonstrated PR; this is consistent with earlier studies in Asian population (25%-42%). 22,23 Furthermore, although SD status was not achieved in most patients, those demonstrating PD were notably few. These findings are consistent with global and Asian studies, 20,22,23 which supports the therapeutic advantage of bortezomib when introduced early as salvage treatment in the course of disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the evaluable Taiwanese patients with MM, the majority demonstrated PR; this is consistent with earlier studies in Asian population (25%-42%). 22,23 Furthermore, although SD status was not achieved in most patients, those demonstrating PD were notably few. These findings are consistent with global and Asian studies, 20,22,23 which supports the therapeutic advantage of bortezomib when introduced early as salvage treatment in the course of disease.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Furthermore, although SD status was not achieved in most patients, those demonstrating PD were notably few. These findings are consistent with global and Asian studies, 20,22,23 which supports the therapeutic advantage of bortezomib when introduced early as salvage treatment in the course of disease. It should be noted here that although studies have demonstrated that higher response quality is associated with longer response duration and survival, 26-28 not all studies show an absolute benefit of achieving CR, and there may exist a subgroup of patients who may obtain prolonged survival often without ever achieving CR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in contrast to proteasome inhibitors, E1 enzyme inhibitors should not lead to the formation of aggresomes, which are known to limit the therapeutic efficacy of bortezomib and carlzomib in both hematological malignancies and solid tumors. [10][11][12][13][14][15][16][17][20][21][22][23][24] Specically, this paper reports the discovery of ABP A3, a dual inhibitor of the ubiquitin-and Nedd8-activating E1 enzymes, which inhibits both Nedd8-dependent and Nedd8-independent ubiquitin conjugation and protein degradation. We then used these probes to investigate the therapeutic potential of the UPS system to treat solid tumors using A549 cell line (non-small cell lung cancer) as a model system.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, proteasome inhibitors have shown limited clinical efficacy in treating multiple myeloma. [10][11][12] These limited responses are in part due to the alternative degradation of misfolded proteins via the aggresomal pathway. [13][14][15][16][17] The aggresomal pathway clears misfolded proteins by delivering misfolded proteins to the lysosome, thereby alleviating proteotoxic stress and contributing to cell survival.…”
Section: Introductionmentioning
confidence: 99%